The library users' perceptions of relevance to the information content of a document from different document representation - Paglicawan, Maricar V.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2002)
Document representations are the immediate tools used by library users, which provide information about the original documents they represent. This study focused on the most common document representation: catalog entries, abstracts, and index terms.
The following were the major findings of the study: 1. ILIS and Psychology students commonly use catalog entries when undertaking research. 2. Based on the students' experiences, on the average, catalog entries are found to be the most useful. Majority of the ILIS students found abstracts to be the most useful document representation while majority of the psychology students listed down catalog entries to be the most useful. 3. In terms of relevance to its original document, students perceived abstracts as the most useful document representation. 4. Majority of the students believe that the relevance of document representation is related to their provided length of information. 5. There was no big difference in the perceptions of both the ILIS and psychology students. The only difference is that the ILIS students were more familiar with the document representations other than the catalog entries, which is the most common tool among students. 6. Based on the activity given, students perceived abstract as having the highest relevance to the original documents among documents representations.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Catalogs -- Use studies